Review—MoSe2 Nanostructures and Related Electrodes for Advanced Supercapacitor Developments. Issue 1 (1st January 2022) - Sha, Rinky; Maity, Palash Chandra; Rajaji, Umamaheswari; Liu, Ting-Yu; Bhattacharyya, Tarun Kanti
Abstract : Molybdenum diselenide (MoSe2 ), an in-organic analog of graphene, is considered a rising star in the family of transition-metal dichalcogenides (TMDs) because of its stable covalent Mo–Se bond, good catalytic properties, huge specific surface area, higher electrical, multivalent oxidation states of transition metal ions, and its ability to be intercalated with suitably-sized metal atoms or organic molecules to modify their physical properties with a distinguishing layered structure. It is being projected as the next-generation 2D layered nano-material for many energy storage-conversion applications. This review covers the properties, functionalization of MoSe2, and their applications in supercapacitors, discussing the current developments of MoSe2 and its nano-composites-based supercapacitors, providing emphasis to the capacitive performances which comprise of specific capacitance/ capacity, cyclic lifespan, energy density, power density, rate capability, and their practicality in the real environments. Fundamental charge-storage mechanisms are also discussed to provide better insight into how MoSe2 is ascribed to each supercapacitor. Wherever applicable, limitations of the existing approaches and future outlook are also described.